Genetic analysis identifies the SLC4A3 anion exchanger as a major gene for short QT syndrome - Christiansen, Morten Krogh; Kjær-Sørensen, Kasper; Clavsen, Natacha C.; Dittmann, Sven; Jensen, Maja Fuhlendorff; Guldbrandsen, Halvor Østerby; Pedersen, Lisbeth Nørum; Sørensen, Rikke Hasle; Lildballe, Dorte Launholt; Müller, Klara; Müller, Patrick; Vogel, Kira; et al. (Heart rhythm, 2023)
Background - A variant in the SLC4A3 anion exchanger has been identified as a novel cause of short QT syndrome (SQTS), but the clinical importance of SLC4A3 as a cause of SQTS or sudden cardiac death remains unknown. - Objective - The purpose of this study was to investigate the prevalence of potential disease-causing variants in SQTS patients using gene panels including SLC4A3. - Methods - In this multicenter study, genetic testing was performed in 34 index patients with SQTS. The pathogenicity of novel SLC4A3variants was validated in a zebrafish embryo heart model. - Results - Potentially disease-causing variants were identified in 9 (26%) patients and were mainly (15%) located in SLC4A3: 4 patients heterozygous for novel nonsynonymous SLC4A3 variants—p.Arg600Cys, p.Arg621Trp, p.Glu852Asp, and p.Arg952His—and 1 patient with the known p.Arg370His variant. In other SQTS genes, potentially disease-causing variants were less frequent (2× in KCNQ1, 1× in KCNJ2, and CACNA1C each). SLC4A3 variant carriers (n = 5) had a similar heart rate but shorter QT and J point to T wave peak intervals than did noncarriers (n = 29). Knockdown of slc4a3 in zebrafish resulted in shortened heart rate-corrected QT intervals (calculated using the Bazett formula) that could be rescued by overexpression of the native human SLC4A3-encoded protein (AE3), but neither by the mutated AE3 variants p.Arg600Cys, p.Arg621Trp, p.Glu852Asp nor by p.Arg952His, suggesting pathogenicity of these variants. Dysfunction in slc4a3/AE3 was associated with alkaline cytosol and shortened action potential of cardiomyocytes. - Conclusion - In about a quarter of patients with SQTS, a potentially disease-causing variant can be identified. Nonsynonymous variants in SLC4A3 represent the most common cause of SQTS, underscoring the importance of including SLC4A3 in the genetic screening of patients with SQTS or sudden cardiac death.